A Comparison Study between Theophylline and Placebo in Passage of Ureteral Stones - Tadayyon, Farhad; Yazdani, Mohammad; Ebadzadeh, Mohammadreza (Urology Journal, 2009)
Purpose: Considering the high prevalence of urinary system stones and that non-medical treatments have more costs and side effects, we decided to evaluate the effect of theophylline in the passage of ureteral stones. Â Materials and Methods: One hundred and fifty patients with ureteral stones were assigned into groups A and B, whose age, sex, size of stone, and location of stone were matched together. Patientsâ€™ ages ranged from 17 to 67 years. In group A theophylline (200 mg BID) was administered and group B received placebo for six weeks. Both groups were followed up by visits every fortnight and radiological assessment was performed at the end of the sixth week. The proportion of patients whose stones were passed was compared between the two groups. Result: In group A with theophylline consumption 46 out of 75 (61.3%) passed their stones. The mean duration between the initiation of the treatment with theophylline and stone passage was18.3 days. In group B with placebo, the stone passage occurred in 31 out of 75 (41.3%) patients (p Conclusion: With regard to the findings of this study, it seems that theophylline can increase the rate of ureteral stone passage and as well, accelerate it.